Can knowledge-based assets increase organizational performance? Evidence from village financial institutions in Bali, Indonesia - Ni Made Rai Juniariani; Noorlailie Soewarno; Alfa Rahmiati (Problems and Perspectives in Management)
The purpose of this study is to examine the effect of knowledge-based assets, namely the ability to integrate knowledge and intellectual capital, on organizational performance. This study uses a survey approach with a sample of 313 LPDs (village financial institutions) in the province of Bali, represented by the heads of LPDs. The heads of LPDs were chosen because they are operational executors of LPD and are responsible for the development of LPD management. Data were collected using questionnaires distributed directly to LPD heads. The results of this study indicate that organizational performance is substantially and positively influenced by human capital and relational capital. Spiritual capital does not have a substantial influence on organizational performance, whereas structural capital has a negative effect. Further analysis revealed that knowledge integration capability can mediate the influence of human capital, structural capital, and relational capital. However, it cannot mediate the influence of spiritual capital on organizational performance. The research results strengthen the intellectual capital theory that intellectual capital can increase organizational performance if integrated with ability or dynamic knowledge.